OCORRÃŠNCIA DE Fidicinoides pauliensis BOULARD & MARTINELLI, 1996 (HEMIPTERA: CICADIDAE) EM CAFEEIRO EM TAPIRATIBA, SP - Santos, Rodrigo Souza; Martinelli, Nilza Maria (REVISTA DE AGRICULTURA, 2015)
OCORRÃŠNCIA DE Fidicinoides pauliensis BOULARD & MARTINELLI, 1996 (HEMIPTERA: CICADIDAE) EM CAFEEIRO EM TAPIRATIBA, SP